Tailoring the self-assembly of linear alkyl chains for the design of advanced materials with technological applications - Hoppe, Cristina Elena (2018)
The self-assembly of n-alkyl chains at the bulk or at the interface of different types of materials and substrates has been extensively studied in the past. The packing of alkyl chains is driven by Van der Waals interactions and can generate crystalline or disordered domains, at the bulk of the material, or self-assembled monolayers at an interface. This natural property of alkyl chains has been employed in recent years to develop a new generation of materials for technological applications. These studies are dispersed in a variety of journals. The purpose of this article was to discuss some selected examples where these advanced properties arise from a process involving the self-assembly of alkyl chains. We included a description of electronic devices and new-generation catalysts with properties derived from a controlled two-dimensional (2D) or three-dimensional (3D) self-assembly of alkyl chains at an interface. Then, we showed that controlling the crystallization of alkyl chains at the bulk can be used to generate a variety of advanced materials such as superhydrophobic coatings, shape memory hydrogels, hot-melt adhesives, thermally reversible light scattering (TRLS) films for intelligent windows and form-stable phase change materials (FS-PCMs) for the storage of thermal energy. Finally, we discussed two examples where advanced properties derive from the formation of disordered domains by physical association of alkyl chains. This was the case of photoluminescent nanocomposites and materials used for reversible optical storage.